Blood, Sweat and Tears of a CEO (S/O 14690) - Hussin, Muhammad Rosni Amir; Abd Mutalib, Hafizah; Che Pak, Nur Azliani Haniza; Sulaiman, Aryati Juliana (UUM, 2021)
The teaching case tells about the journey of the protagonist, Mr AKC, who ran a furniture manufacturing business. PBU. The company started as a small wood-based and metal-based furniture producer, and sales were made through retail and rental of furniture models for the education sector. More than two decades after the incorporation, PBU made quite a success with the inclusion of hospital furniture in its product line. The case highlights the good leadership characteristics possessed by Mr AKC in ensuring th·e success of PBU. In this case, students may observe the quality of a leader cum entrepreneur in ensuring the business to soar. The case is categorised as an illustrative/best practice, in the field of operation and strategic management.